2015
DOI: 10.3399/bjgp15x687433
|View full text |Cite
|
Sign up to set email alerts
|

Improving management and effectiveness of home blood pressure monitoring: a qualitative UK primary care study

Abstract: BackgroundSelf-monitoring blood pressure (SMBP) is becoming an increasingly prevalent practice in UK primary care, yet there remains little conceptual understanding of why patients with hypertension engage in self-monitoring. AimTo identify psychological factors or processes prompting the decision to self-monitor blood pressure. Design and settingA qualitative study of patients previously participating in a survey study about SMBP from four general practices in the West Midlands. MethodTaped and transcribed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Shorter monitoring schedules were the preferred option of patients in this study. Given evidence that few additional data are gained from longer regimens, 12 coupled with evidence that patients may drift from pre-specified advice, 8 a simpler approach might be appropriate. Rather than asking for 28 readings taken at specific times (for example, two in the morning and two in the evening over 7 days), GPs might gain better adherence by emphasising that a flexible regimen will give similar data provided that at least 3 days of self-monitoring are included.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Shorter monitoring schedules were the preferred option of patients in this study. Given evidence that few additional data are gained from longer regimens, 12 coupled with evidence that patients may drift from pre-specified advice, 8 a simpler approach might be appropriate. Rather than asking for 28 readings taken at specific times (for example, two in the morning and two in the evening over 7 days), GPs might gain better adherence by emphasising that a flexible regimen will give similar data provided that at least 3 days of self-monitoring are included.…”
Section: Implications For Practicementioning
confidence: 99%
“…[5][6][7] However, self-monitoring largely takes place within the privacy of the patient's home, and thus can be hidden from the patient's clinical care provider. 8 Although the National Institute for Health and Care Excellence (NICE) 1 and international guidelines 3,9 recommend a week of readings for diagnosis, most primary care healthcare professionals (HCPs) use self-monitoring for ongoing management, 10 for which there are no evidence-based recommendations on what type of self-monitoring schedule to implement. Consequently, wide variation in practice has been reported by both patients and HCPs.…”
Section: Introductionmentioning
confidence: 99%
“…An easing of the intensity of patient-directed SMBP has been observed elsewhere. 25 A qualitative study found that clinicians supported differing schedules for the purposes of diagnosis and ongoing management of hypertension, although the views of patient participants for this theme were not reported. 26 Solid-cuff monitors, either in waiting rooms or in pharmacies -as seen in North America -may have a role in hypertension diagnosis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This study reiterates the difficulties of supporting patients undertaking out-ofoffice monitoring in routine primary care. 25 A recent meta-analysis and individual patient data analysis concluded that selfmonitoring alone was not associated with e841 British Journal of General Practice, December 2018 lower BP. 27 However, when combined with co-interventions such as patient education or lifestyle counselling, it resulted in clinically significant reductions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Home monitoring, as nicely illustrated in this study, provides the prescribing clinician with early reliable information on the therapeutic response and the need for dose escalation or addition of further antihypertensive agents [20,21]. The technique can also prompt patients to return to the clinic earlier if they are concerned about persistently elevated home readings despite therapy, or they might be facilitated in titrating their own medications as instructed [22,23]. It allows a sharing of responsibility with the patient.…”
mentioning
confidence: 97%